George & Sylvia : A Tale Of True Love - Michael Coleman (Little Tiger Press, 2000)
George loves Sylvia and Sylvia loves George but neither of them is able to tell each other how they feel. George thinks he is too big and too fat for Sylvia and Sylvia believes she is too small and skinny for George.
Keywords: Circle Time Book - Humour -- Circle Time Book - Humour